Reflections on Critical Thinking in the Nursing Process and Japanese Nurse Education - Misae Ito; Kyoko Murakami; Satoko Ono; Margaret McMillan (Halla Newcastle Education and Research Center, 2021)
This reflective paper examines nurse education in Japan in the context of a rapidly changing and increasingly complex health care environment. The purpose of this paper is to i) provide an overview of Japanese changing nursing discipline ii) make an appraisal of whether the core elements of the Nursing Process are sufficient to ensure optimal nursing responses to person-centered care, iii) examine issues around the management of change that need further exploration if nurses in Japan are to continue to have a central role in responding to consumer/patient needs. Following an overview of the current nurse education system and supporting nursing organizations we critically examine the existing curriculum and models of practice including the nursing process in the light of the need for practice-ready reflective nurses.